STRATEGI PEMBELAJARAN BAHASA INDONESIA DALAM MENINGKATKAN KEAKTIFAN SISWA: STUDI DI SMAN 8 MUARO JAMBI - Gina Azzahrah; Zahra Maryana Safitri; Helty; Liza Septa Wilyanti (Jurnal Lazuardi, 2026)
This study aims to describe Indonesian language learning strategies in increasing student activeness at SMAN 8 Muaro Jambi using biographical text material. The method used is descriptive qualitative with data collection through direct observation, semi-structured interviews with Indonesian language teachers, and documentation. The results show that teachers implement Problem-Based Learning (PBL) strategies combined with varied methods including lectures, questions and answers, discussions, practice, and simulation. This strategy is proven effective in encouraging student activeness, as evidenced by the fulfillment of all 20 observation indicators across five components: learning planning, learning implementation, student activities, learning media, and evaluation. Obstacles encountered include low reading interest, regional language interference, and the influence of gadgets. These findings indicate that PBL with adaptive media and structured evaluation can increase student activeness in Indonesian language learning.